UPAYA LEMBAGA ADAT BATAK DALIHAN NATOLU DALAM PENCEGAHAN KEKERASAN PADA ANAK DALAM KELUARGA DI KECAMATAN PANDAN KABUPATEN TAPANULI TENGAH - Conny Ofta Tiani Br Tompul; Erdianto Erdianto; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Children are often victims of violence so that family has a very important role for children, because inessence of the family is the first place for children to acquire knowledge, mental development, and personalityformation, while the purpose of this research is to see the efforts of the Dalihan Natolu Batak TraditionalInstitute (LABDN) in preventing violence against children in the family. The customary law that applies, namelyDalihan Natolu, is a cultural system in which for the Batak people the values it contains are used as a way oflife and at the same time a source of motivation for behavior.The type of legal research used by the author is a sociological legal research. Sociological law researchis research that wants to see the correlation between law and society, so as to be able to reveal the effectivenessof the enactment of law in society. The research location was conducted in Pandan District, Central TapanuliRegency. Sources of data used are primary data and secondary data, data collection techniques in this study arequestionnaires, interviews, and literature review, and concluded with a deductive thinking method.From the results of this study it was concluded that First, efforts were made to socialize to the communityabout violence against children, working with traditional elders to apply local wisdom values, giving customarysanctions to perpetrators of violence against children. Second, the obstacles experienced by thecommunity/families are not reporting, the view that violence is for educating children, regional conditions andlack of budget.The author's suggestion is that the government should pay more attention to the existence of the DalihanNatolu Batak Traditional Institution, special institutions dealing with children are able to work together withtraditional institutions to jointly prevent child abuse and everyone should care more about the existence ofchildren so that they are wiser in educating children.Keywords : Dalihan Natolu Batak Traditional Institute – Prevention – Violence of children